Effect of artificial respiratory muscle training in patients with chronic obstructive pulmonary disease - Decha Pinkaew (2018)
© 2018, Walailak University. All rights reserved. Chronic obstructive lung disease (COPD) is a chronic lung pathology that leads to respiratory muscle weakness and decreased function capacity. Patients need to have pulmonary rehabilitation to increase respiratory muscle strength. The aim of the study was to assess the effect of artificial respiratory muscle training (ARMT) on respiratory muscle function and exercise performance in chronic obstructive pulmonary disease (COPD). Thirty patients in the mild to moderate COPD stage were randomly classified into an ARMT (n = 10), a control group (n = 10), and a standard respiratory muscle training group (SRMT; n = 10) by following the blind procedure. The control group received no training. The training groups, however, were trained at home for 30 min per day, every day, for 6 weeks. The measurement analyses included spirometry, an inspiratory muscle strength examination, and an exercise performance test. Exercise performance was evaluated by a 6 min walk test (SWT). The results showed that the maximal inspiratory pressure (PImax) and the maximal expiratory pressure (PEmax) were observed to have significantly increased in both the ARMT group and the SRMT group compared with the control group (p < 0.05). Moreover, the ARMT group was found to have significantly increased the 6 min walking distance in comparison with the control group. However, the ARMT group and the SRMT group did not differ significantly in those parameters. We conclude that it would be possible for the ARMT group among COPD patients to have improved respiratory muscle strength and increased capacity to walk.